Analisis fitokimia dan kromatografi lapis tipis ekstrak etanol daun rosella (Hibiscus sabdariffa L.) - Tira Risa Oktapiya; Nofran Putra Pratama; Nur'aini Purnamaningsih (Sasambo Journal of Pharmacy, 2022)
Rosella (Hibiscus sabdariffa L) is a plant belonging to the Malvaceae family. This plant is widely used as herbal medicine. Rosella leaves have many compounds that can function as antioxidants and antibacterials. As a crude material for traditional medicine, it is necessary to know the content of secondary metabolites contained in rosella leaves both quantitatively and qualitatively as one of the standardization parameters. The objective of this study was to determine the content of secondary metabolites contained in the ethanolic extract of rosella leaves through phytochemical analysis and Thin Layer Chromatography. Rosella leaf extraction was carried out by maceration method using 70% ethanol as solvent. Testing the content of secondary metabolites in the ethanolic extract of rosella leaves was carried out by phytochemical screening. Furthermore, the TLC test was carried out to confirm the presence of a positive group of compounds on phytochemical screening. Phytochemical screening from rosella leaves extract revealed the presence of alkaloids, flavonoids, saponins and tannins. The TLC system used in this study was able to separate the phytochemical content and gave positive results confirming the phytochemical screening results. The eluent used was chloroform:methanol:acetic acid with a ratio of 14:2:1 obtained spots with an Rf of 0.737 which is similar to the Rf standard of quercetin which is 0.762.